Addressing the Basic Infrastructure Gap in Strategic Areas of West NusaTenggara Province - Tribuana Tungga Dewi (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
This study examines the basic infrastructure gap in the Provincial Strategic Areas of West Nusa Tenggara, Indonesia, where investment-oriented spatial development has progressed faster than the provision of essential public services. The designation of eleven Provincial Strategic Areas under the 2024–2044 Regional Spatial Plan has strengthened development agendas in tourism, industry, agribusiness, and environmental conservation. However, communities around these areas still face unequal access to safe drinking water, proper sanitation, and accredited health facilities. Using a qualitative policy case study with a descriptive-prescriptive design, this research analyzed spatial planning documents, regional development plans, minimum service standard reports, sectoral documents, and stakeholder assessments. The analysis combined the Urgency, Seriousness, and Growth matrix, Fishbone root-cause analysis, and policy-option assessment. The findings show that access to safe drinking water reached 58%, proper sanitation 42%, and accredited health facilities only 31%, indicating a substantial mismatch between strategic-area development and basic service fulfillment. The USG analysis identified the basic utility infrastructure crisis as the highest-priority problem. Root-cause analysis further shows that the gap is shaped by regulatory weakness, institutional fragmentation, fiscal limitation, and spatial-ecological pressure. This study contributes to sustainable infrastructure and regional governance debates by positioning basic infrastructure as the key mechanism through which strategic-area development either reduces or reproduces regional disparities. The study recommends strategic-area-specific Minimum Service Standards, a functional Regional Governance Board, and a Sustainable Infrastructure Fund to align investment growth with equitable, coordinated, and resilient service delivery